The clinical use of a preparation based on phyto-oestrogens in the treatment of menopausal disorders - Russo, R.; Corosu, R. (Acta Biomedica Atenei Parmensis, 2003)
In order to evaluate the efficacy of soya isoflavones (genistein and daidzein) in the treatment of the principal menopausal disorders, a double blind randomized study was performed on a sample of 50 women (with an average age of 53,3±3,1 years) with Climateric syndromereferred to the I Clinica Ostetrica e Ginecologica, Policlinico Umberto I, Roma. The research protocol involved the random subdivision of the enrolled sample into two groups of 25 women, group 1 (with an average age of 53,3±3,5 years, and an average menopausal age of 51,6±1,8 years) and group 2 (with an average age of 53,1±2,9 years, and an average menopausal age of 51,3±1,2 years), who were to receive treatment for three months with the product being studied and with a placebo. After the three-month period, as an additional check, the group initially treated with the placebo would move to the phyto-oestrogens and viceversa. All of the patients were subjected to a series of clinical and instrumental examinations and were asked to fill in a questionnaire concerning their complaints, at the start, at halfway (third month) and at the end (sixth month) of the trial. The results of the evaluation of the questionnaires performed on the 47 patients who had completed the trial showed, in the first three months, an improvement in the symptoms (hot flushes) in 11 patients treated with phyto-oestrogens against 6 patients from the group that received only the placebo. In the second three-month period the hot flushes reappeared in 4 of the 11 patients who had previously seen improvements and had then passed to the placebo. In contrast, the group that passed to the phyto-oestrogens, after treatment with the placebo, experienced the disappearance of hot flushes in 11 women, including the 6 who had already improved in the first three months. There was no significant reduction in anxiety, insomnia or vaginal dryness. None of the enrolled patients indicated complaints linked to the treatment. It can be concluded that the use of a product based on phyto-oestrogens, such as the one experimented, can lead to a significant reduction in some of the disorders linked with the menopause, especially hot flushes.